2008
DOI: 10.1525/mp.2008.26.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Range of Tuning for Tones With and Without Vibrato

Abstract: PREVIOUS STUDIES ON VIBRATO PITCH HAVE attempted to determine the "principal pitch" of vibrato tones and not the range of tuning for such tones in a melodic context. This study investigates the range of acceptable tuning (RAT) for tones with and without vibrato, using repeating ascending and descending three-tone arpeggios. The second tone in each sequence was modulated or unmodulated with an initial pitch that was flat or sharp. With each repetition the pitch of the second tone increased or decreased by 3 cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 16 publications
4
29
0
Order By: Relevance
“…The performed pitches in response to vibrated tone stimuli were near the mean frequencies of the vibrato for both vibrato and non-vibrato responses. The vibrato responses were a few cents lower than non-vibrated responses, a result that appears to corroborate recent investigation of listeners' perception of vibrato tones van Besouw et al, 2008). These results are consistent as well with Study 1 using the method of paired comparisons, at least for the violin.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The performed pitches in response to vibrated tone stimuli were near the mean frequencies of the vibrato for both vibrato and non-vibrato responses. The vibrato responses were a few cents lower than non-vibrated responses, a result that appears to corroborate recent investigation of listeners' perception of vibrato tones van Besouw et al, 2008). These results are consistent as well with Study 1 using the method of paired comparisons, at least for the violin.…”
Section: Discussionsupporting
confidence: 90%
“…This perhaps indicates that these musicians heard pitches of vibrato tones one or two cents lower than the arithmetic mean of the vibrato. This outcome also appears to correspond with the conclusion of van Besouw et al (2008), who used synthesized tones and found that the range of acceptable tuning for vibrato tones was approximately 10 cents wider and predominantly in the flat direction compared to non-vibrato tones.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…In this case, the difference between the predicted and observed mean values are greater for the u profiles, reaching 13 Hz (11 cents) for p f ¼ 24%. Except for this last case, the differences are all within the RAT (range of acceptable tuning) for vibrato tones, 29 which goes up to 10 cents, so that a vibrato with carrier frequency of up to 10 cents flatter than the fundamental frequency of a tone without vibrato is still perceived as being in tune. The functional form of f con vs p f has a maximum departure from the geometric mean between p f ¼ 50% and p f ¼ 70% for experiment 1 and for a wide range of c values, which agrees with the maximum departure for the perceived pitch that occurs for values p f ¼ 55% and p f ¼ 75%.…”
Section: A Comparison Of Pitch Modelsmentioning
confidence: 86%
“…Only a few cycles of vibrato may appear in short sung notes. The perceived pitch of such notes appears to be a function of the vibrato phase at the end of the note [31], but when sinusoids rather than synthesized /a/ vowels are used, there are variations in the pitch changes perceived [32].…”
Section: Vibratomentioning
confidence: 99%